ONC201 induces cell death in pediatric non-Hodgkin's lymphoma cells - Talekar, Mala K (Cell Cycle, 2015)
ONC201/TIC10 is a small molecule initially discovered by its ability to coordinately induce and activate the TRAIL pathway selectively in tumor cells and has recently entered clinical trials in adult advanced cancers. The anti-tumor activity of ONC201 has previously been demonstrated in several preclinical models of cancer, including refractory solid tumors and a transgenic lymphoma mouse model. Based on the need for new safe and effective therapies in pediatric non-Hodgkin's lymphoma (NHL) and the non-toxic preclinical profile of ONC201, we investigated the in vitro efficacy of ONC201 in non-Hodgkin's lymphoma (NHL) cell lines to evaluate its therapeutic potential for this disease. ONC201 caused a dose-dependent reduction in the cell viability of NHL cell lines that resulted from induction of apoptosis. As expected from prior observations, induction of TRAIL and its receptor DR5 was also observed in these cell lines. Furthermore, dual induction of TRAIL and DR5 appeared to drive the observed apoptosis and TRAIL expression was correlated linearly with sub-G1 DNA content, suggesting its potential role as a biomarker of tumor response to ONC201-treated lymphoma cells. We further investigated combinations of ONC201 with approved chemotherapeutic agents used to treat lymphoma. ONC201 exhibited synergy in combination with the anti-metabolic agent cytarabine in vitro, in addition to cooperating with other therapies. Together these findings indicate that ONC201 is an effective TRAIL pathway-inducer as a monoagent that can be combined with chemotherapy to enhance therapeutic responses in pediatric NHL.